Kajian Ikonografi dan Ikonologi Lukisan Raden Saleh : “Gouvernour-Generaal Daendels en De Grote Postweg” (1838) - Aditya Nirwana (Citradirga : Jurnal Desain Komunikasi Visual dan Intermedia, 2019)
Studies in Raden Saleh's painting "Gouvernour - Generaal Daendels en de Grote Postweg" (1838) using the methods of historical research , with Erwin Panofsky’s Iconology and iconography theoretical approaches. As for the study of literature, investigation is conducted at the documentation centers or art archives centers. The conclusions obtained in this study is the first ; the primary meaning of this painting which formed from factual meaning and exspressional meaning is the Daendels’s superiority, drawn in the Romanticism style. The second, on the iconographic analysis, this painting expresses the theme of political conflict and tragedy caused by the oppression of colonialism and imperialism, or the concept of suppression. The third, the painting is a symbols of his crystallized criticism or resistance against oppression by the Netherlands Indie government, but the expression is "disguised" by him in a portrait painting.